Analysis of Digital Capability in Building Entrepreneurial Resilience among University Students - Lik Anah; Amer, Afizan; Nisful Laili, Choirun; Sugi Rahayu Ningsih, Lilis; Santoso, Rohmad Prio (Corolla International Conference, 2025)
As agents of change, students of the Faculty of Economics at UNHASY are required not only to master conventional economic theories but also to adapt and compete in the constantly evolving digital ecosystem. Digital capability serves as a fundamental foundation that enables entrepreneurs to explore digital opportunities and adjust to market dynamics. Entrepreneurial resilience refers to the capacity of an entrepreneur not only to survive but also to actively adapt and grow. This study employed a descriptive method with a qualitative approach to gain an in-depth understanding of students’ experiences and perceptions in building resilience through their digital capabilities. The findings reveal that digital capability constitutes a critical foundation in shaping entrepreneurial resilience and adaptability among students. The integration of digital capability with entrepreneurial resilience, reinforced by the pesantren values distinctive to UNHASYsuch as honesty, perseverance, and collaboration can serve as guiding principles in running a business.